Clock genes associate with white matter integrity in depressed bipolar patients. (7th February 2017) - Bollettini, Irene; Melloni, Elisa Maria Teresa; Aggio, Veronica; Poletti, Sara; Lorenzi, Cristina; Pirovano, Adele; Vai, Benedetta; Dallaspezia, Sara; Colombo, Cristina; Benedetti, Francesco
ABSTRACT: Human genetic studies have implicated specific genes that constitute the molecular clock in the manifestation of bipolar disorder (BD). Among the clock genes involved in the control system of circadian rhythms, CLOCK 3111 T/C and Period3 (PER3) influence core psychopathological features of mood disorders, such as patterns of sleep, rest, and activity, diurnal preference, cognitive performances after sleep loss, age at the onset of the illness, and response to antidepressant treatment. Furthermore, several studies pointed out that bipolar symptomatology is associated with dysfunctions in white matter (WM) integrity, suggesting these structural alterations as a possible biomarker of the disorder. We hypothesise that CLOCK and PER3 polymorphisms could be potential factors affecting WM microstructure integrity in bipolar patients. The relationship between these clock genes and DTI measures of WM integrity in a sample of 140 (53 M; 87 F) patients affected by BD type I was studied. Tract-based spatial statistics analyses on DTI measures of WM integrity were performed for each clock gene polymorphism, between the genetic groups. We accounted for the effect of nuisance covariates known to influence WM microstructure: age, sex, lithium treatment, age at the onset of the illness, and the number of illness episodes. We found that compared to T homozygotes, CLOCK C carriers showed a widespread increase of the mean diffusivity in several WM tracts. Compared with PER3 5/5 homozygotes, PER3 4/4 homozygotes showed significantly increased radial diffusivity and reduced fractional anisotropy in several brain WM tracts. No significant difference was observed between heterozygotes and the other subgroups. Altogether, this pattern of results suggests WM disruption in CLOCK C carrier and in PER3 4 homozygotes. Sleep promotes myelination and oligodendrocyte precursor cell proliferation and associates with higher expression of genes coding for phospholipid synthesis and myelination in oligodendrocytes. These clock genes play a pivotal role in maintaining circadian rhythms and the sleep-wake cycle. Thus, it may be suggested that CLOCK rs1801260*C and PER3 4/4 influence myelination processes by regulating sleep quality and quantity.